Flow mixing during peripheral veno-arterial extra corporeal membrane oxygenation – A simulation study. (11th April 2017) - Stevens, M.C.; Callaghan, F.M.; Forrest, P.; Bannon, P.G.; Grieve, S.M.
Abstract: Peripheral veno-arterial extra-corporeal membrane oxygenation (ECMO) is an artificial circulation that supports patients with severe cardiac and respiratory failure. Differential hypoxia during ECMO support has been reported, and it has been suggested that it is due to the mixing of well-perfused retrograde ECMO flow and poorly-perfused antegrade left ventricle (LV) flow in the aorta. This study aims to quantify the relationship between ECMO support level and location of the mixing zone (MZ) of the ECMO and LV flows. Steady-state and transient computational fluid dynamics (CFD) simulations were performed using a patient-specific geometrical model of the aorta. A range of ECMO support levels (from 5% to 95% of total cardiac output) were evaluated. For ECMO support levels above 70%, the MZ was located in the aortic arch, resulting in perfusion of the arch branches with poorly perfused LV flow. The MZ location was stable over the cardiac cycle for high ECMO flows (>70%), but moved 5 cm between systole and diastole for ECMO support level of 60%. This CFD approach has potential to improve individual patient care and ECMO design.